Assessing the Efficacy of Progesterone as a Therapeutic Agent for Spinal Myelitis in Dogs: A Comprehensive Study - P K, Ramkumar; M Saravanan,; Karthika, K; Premalatha , N; Velusamy, R; Yogeshpriya, S (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This research focused on the treatment of confirmed neurological cases of myelitis in dogs. The control group (Group I) consisted of apparently healthy dogs of different breeds, ages, and sexes undergoing routine health check-ups. The study included Group II, treated with a standard glucocorticoid treatment protocol (n=6), and Group III, treated with progesterone (n=6). Parameters considered for analysis included breed, age, and sex of the animals. Clinical assessments involved recording of clinical signs, hematobiochemical analysis, cerebrospinal fluid (CSF) analysis, radiography. The selected cases underwent treatment with glucocorticoids as per standard protocol and were compared with those treated using progesterone. The treatment trial spanned a duration of 14 days. Evaluation of the treatment protocols included assessments of clinical recovery, hemato-biochemical changes, serum progesterone levels, and serum Neuron Specific Enolase levels on day 0 (pretreatment), 7th day, and 14th day post-treatment. CSF analysis, including progesterone assay, was conducted on day 0 and the 14th day post-treatment. The overall incidence of various neurological disorders causing ataxia in dogs was 2.38%. Among these cases, 59% were encephalitis, 24% were myelitis, and 17% were neuromyopathies. The progesterone treatment protocol exhibited significant therapeutic efficacy for myelitis (spinal cord injury) cases.
Keywords: Glucocorticoid; Neuron specific enolase; Myelitis; Prednisolone; Progesterone